1976
DOI: 10.1002/1097-0142(197611)38:5<2135::aid-cncr2820380543>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasms of the central nervous system.Incidence and population selectivity in the Washington DC, metropolitan area

Abstract: During the period 1960 through 1969, 990 primary neoplasms of the central nervous system were diagnosed in hospitals in the Washington, DC, Standard Metropolitan Statistical Area (SMSA). All cases were identified according to age, race, sex, histologic type, and date of diagnosis. A West African composite of 253 cases was used for comparison. In the Washington SMSA, the age‐adjusted incidence rates were: for Caucasians 5.5 in males and 3.6 in females and for Negroes 4.8 in males and 3.4 in females per 100,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
1

Year Published

1978
1978
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“…The mean ages at diagnosis differ in the reported series, presumably because of the very different upper age limits for childhood, the upper limit varying between 12 and 20 years (Matson, 1969;Koos and Miller, 1971;Till, 1975;Yates and Becker, 1976;Dohrman et al, 1976a, b;Heshmat et al, 1976;Schoenberg et al, 1976). The few studies using the usual paediatric upper limit for childhood of 15 years of age also show varying age rates of incidence.…”
Section: Discussionmentioning
confidence: 90%
“…The mean ages at diagnosis differ in the reported series, presumably because of the very different upper age limits for childhood, the upper limit varying between 12 and 20 years (Matson, 1969;Koos and Miller, 1971;Till, 1975;Yates and Becker, 1976;Dohrman et al, 1976a, b;Heshmat et al, 1976;Schoenberg et al, 1976). The few studies using the usual paediatric upper limit for childhood of 15 years of age also show varying age rates of incidence.…”
Section: Discussionmentioning
confidence: 90%
“…Incidence rates for all CNS tumors, gliomas, and nerve sheath tumors were higher for whites than blacks in Los Angeles, although the meningioma rates were higher in blacks (Preston-Martin, 1989). An earlier report from the Washington, D.C., metropolitan area disclosed higher proportions of meningiomas and pituitary tumors in blacks compared with whites (Heshmat et al, 1976). In the current study, no racial differences were observed in incidence rates for either meningiomas or pituitary tumors.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8][9][10][11] Knowledge of the regional peculiarities of these lesions may, therefore, help in identification of possible risk factors and also in establishing measures for improved diagnosis, treatment, and outcome.…”
mentioning
confidence: 99%